Quality labelling for re-used ICT equipment to support consumer choice in the circular economy - Gavertsson, L, Milios, L. and Dalhammar, C. (Journal of Consumer Policy)
The ever-increasing consumption of natural resources required for the production of consumer electronics, and the growing amount of electronic waste, underline the importance and urgency of extending the lifespan and use of such products. Information and Communication Technology (ICT) remanufacturing is a growing industry, which nonetheless faces several barriers. Consumers often have a perception of re-used and remanufactured products that they are of lesser quality than their new counterparts. To increase consumer confidence, a quality label could be used to communicate quality aspects of re-used ICT equipment. This study investigates the potential of establishing a comprehensive labelling scheme for ICT products, covering criteria on product quality, as a way to support the uptake of re-used and remanufactured products in Sweden. A detailed analysis, through interviews and a literature review of existing re-use certification initiatives in different jurisdictions, highlighted aspects that should be considered for the design and implementation of a labelling scheme, including appropriate marketing, funding sources, establishment of networks, and the necessity of specific quality criteria on ICT products. Interviews with Swedish ICT stakeholders revealed a trade-off between the information communicated by a label of re-used and remanufactured ICT products and the costs to cover and verify these aspects. The Swedish ICT re-use sector is small and it could only benefit from a labelling scheme if there is wide stakeholder participation and government support. Lastly, a quality labelling scheme should be linked to public procurement processes to improve its effectiveness and efficiency.- Reproduced
Keywords: Environmental policy, Labelling, Re-use. Remanufacturing. Resource efficiency